ANALISIS INTERAKSI SOSIAL DAN IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA BERKEBUTUHAN KHUSUS DI SMP IT NURUL ‘ILMI TENGGARONG - Nur Amanah; Maryam; Falisha Ramadhani; Mumtazah Nawar Afifah; Ana Setiyani Mutia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research seeks to examine the dynamics of social interactions and the application of Islamic Religious Education (PAI) instruction for students with special needs at SMP IT Nurul ‘Ilmi Tenggarong. Adopting a qualitative methodology with a descriptive framework, the study focused on participants identified with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD). Information was gathered via direct observation, in-depth interviews, and document review, then processed through an interactive analysis framework involving data condensation, presentation, and inference development. Key results reveal a strong link between social engagement and the learning experience. Learners with autism often struggle with verbal exchange and peer relationships, whereas those with ADHD encounter issues in sustaining focus and managing impulses. Such variations notably impact their involvement in PAI sessions. Flexible instructional methods like straightforward explanations, precise dialogue, and material reinforcement proved more successful in enhancing comprehension. The success of PAI for students with special needs hinges on interpersonal skills, pedagogical techniques, and backing from educational institutions and households. Hence, tailored and adaptable teaching methods are crucial for maximizing these students' capabilities.